Strong blue emission from Er3+ doped in AlxGa1-xN - Wakahara, A; Nakanishi, Y; Fujiwara, T; Okada, H; Yoshida, A; Ohshima, T; Kamiya, T; Kim, YT (WILEY-V C H VERLAG GMBH, 2004)
Er ions are introduced into AlxGa1-xN (0 less than or equal to x less than or equal to 1) by ion implantation to investigate the effect of Al composition on the luminescence properties of 4f(n) inner-shell transitions of Er3+. Strong and sharp emission peaks attributed to the 4f-4f transition of Er3+ are observed in ultra-violet and blue region (400-550 nm) from the samples with AlN molar fraction of x > 0.3. These photoemissions are assigned as P-2(3/2) - I-4(15/2), P-2(3/2) - I-4(13/2), P-2(3/2) - I-4(11/2), and P-2(3/2) - P-4(11/2) transitions, and the 408 nm emission, corresponding to P-2(3/2) - I-4(13/2) transition, is the strongest in the present work. As increasing the Al composition, the intensity of Er3+-related emissions is rapidly increased and the thermal quenching proper-ties is also improved.
Keywords: THIN-FILMS; GAN; PHOTOLUMINESCENCE; CATHODOLUMINESCENCE; ELECTROLUMINESCENCE; LUMINESCENCE; DIODES